2016
DOI: 10.3390/su8070600
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approach to Construction of Benchmarking Network in DEA-Based Stepwise Benchmark Target Selection

Abstract: Abstract:Stepwise benchmark target selection in data envelopment analysis (DEA) is a realistic and effective method by which inefficient decision-making units (DMUs) can choose benchmarks in a stepwise manner. We propose, for the construction of a benchmarking network (i.e., a network structure consisting of an alternative sequence of benchmark targets), an approach that integrates the cross-efficiency DEA, K-means clustering and context-dependent DEA methods to minimize resource improvement pattern inconsiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Irrespective of the advantages of the method, the following limitations of method are; if there appears to be many DMUs and many intermediate ports between each group, the applied method can create some cumbersome where too many benchmark steps may cause significant hurdles in benchmarking practices (Park and Sung 2016). Future research should address this problem to minimize the benchmarking target pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Irrespective of the advantages of the method, the following limitations of method are; if there appears to be many DMUs and many intermediate ports between each group, the applied method can create some cumbersome where too many benchmark steps may cause significant hurdles in benchmarking practices (Park and Sung 2016). Future research should address this problem to minimize the benchmarking target pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies did not conduct benchmarking studies to provide environmental performance of the ports. Limited studies can be found related to benchmarking port efficiency (Hun et al, 2010;Sharma and Yu, 2009;Park and Sung 2016). In line with such motivation, this study will benchmark the environmental efficiency of container ports against best-practices in the U.S ports.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD-DEA, consisting of stratification procedure, attractiveness measure, and progress measure, has proven a helpful method to construct the benchmark-learning pathway for inefficient DMUs [27,28]. Through the benchmark-learning pathway, inefficient DMUs can stepwise improve their efficiencies and reach the terminal frontier [29,30]. Generally, the CD-DEA is developed under radial measure, where the slack variables are not considered.…”
Section: Methodsmentioning
confidence: 99%
“…More applications of DEA can be found in Emrouznejad and Yang [9] and Liu et al [10]. From a functional perspective, DEA is most often used for DMU ranking [11,12] and benchmarking target selection [13,14], and also used for technological forecasting [15] and clustering [16].…”
Section: Introductionmentioning
confidence: 99%